189 Still Hurting Newborn Babies Eight Years after we Found Out!. (October 2012) - Roofthooft, D; Simons, S; Anand, K; Tibboel, D; Dijk, M van
Abstract : Objective: To study whether new pharmacological and non-pharmacological guidelines lowered numbers of painful procedures in neonates and changed the amount and frequency of analgesic therapy as compared to the results of our previous study in 2001. Design: A prospective observational study.Setting: Level III NICU of the Erasmus MC-Sophia Children's Hospital, Rotterdam. Participants Neonates admitted at postnatal ages less than 3 days with length of stay at least 72 hours. Main outcome measures: Number of all potentially painful procedures and analgesic therapy recorded at the bedside during the first 14 days of NICU stay. Results: A total number of 21076 procedures were performed in the 175 neonates studied during 1730 patient-days (mean 12.2). The mean number of painful procedures per neonate per day was 11.4 (SD 5.7), significantly lower than the number of 14.3 (SD 4.0) in 2001 (p<0.001). The use of analgesics was 36.6% compared to 60.3% in 2001. Failed procedures encompassed sixty-three percent of all peripheral arterial line insertions vs. 37.5% in 2001 and 9.1% venipunctures vs. 21% in 2001. Conclusions: The mean number of painful procedures per NICU patient per day declined and analgesic treatment changed to a more tailored or individualized approach. Non-pharmacological pain- or stress reducing strategies like NIDCAP and sucrose were fully embedded in our pain management. As further reduction of the number of painful procedures is unlikely we should explore newer pharmacological agents and apply non-pharmacological interventions more frequently.